Downward Repositioning of Breast Mound with Early Phase Intervention for Autologous Breast Reconstruction Patients - Makoto Shimabukuro; Naohiro Ishii; Naohiko Ikura; Kyoichi Matsuzaki; Kazuo Kishi (Archives of Plastic Surgery)
In breast reconstruction with a flap transfer, symmetry is often difficult to achieve when the contralateral breast projection has a downward peak. Although minimally invasive and effective methods for postoperative correction of the reconstructed breast mound are desirable, none has been comprehensively reported. We devised a correction method comprising downward movement of the reconstructed breast mound using early postoperative dissection and pressure. This method was applied to four patients undergoing primary two-stage ptotic breast reconstruction with a flap transfer. All of their reconstructed breast mounds were positioned above the contralateral side in the early postoperative period. They underwent manual dissection of the upper edge in flaps under local anesthesia 3 weeks after reconstruction or downward pressure correction using a sponge for 6 months or both procedures. The reconstructed breast mound moved 2 to 2.5 cm downward with early postoperative manual dissection or pressure correction using a sponge and moved 3 cm downward with the combination of both dissection and pressure. Manual dissection in the early postoperative period under local anesthesia and compression with a sponge is minimally invasive and useful for the downward correction of the reconstructed breast mound. The combination of dissection and compression provides a greater corrective effect.